ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI VOLUME PRODUKSI DI PERUSAHAAN TAMBANG BATUBARA MENGGUNAKAN REGRESI DATA PANEL DINAMIS - Margareta, Jingga Ayunda (Fakultas Teknik, 2026)
The Indonesian coal mining industry faces a phenomenon where the size of a company's reserves does not always correlate with its production volume. This study aims to analyze the influence of resources, reserves, production costs, and the Reference Coal Price (HBA) on the production volume of coal mining companies in Indonesia, both partially and simultaneously, and to compare the short-term and long-term impacts of each variable. The data used were obtained from the annual reports of 12 coal mining companies and publications from the Ministry of Energy and Mineral Resources for the period 2015–2024. The analytical method used was dynamic panel data regression with the Generalized Method of Moments approach. The model met all specification tests, including the Sargan test (p-value = 0.3227), the Arellano-Bond AR(2) test (p-value = 0.1448), and the unbiased test, with a GMM dependent lag coefficient of 0.266, which falls between the FEM (0.199) and PLS (0.577) values. The partial test results show that the dependent lag, resources, reserves, and production costs have a positive and significant influence on production volume at a significance level of 5%, with production costs as the most dominant variable (z = 14.94), while HBA has no significant influence (p-value = 0.417). Simultaneously, all independent variables have a significant influence on production volume with an Adjusted R² of 0.9647. The long-term influence of each variable is greater than its short-term influence, with short-term and long-term elasticities of production costs of 0.642 and 0.875, respectively, resources of 0.193 and 0.263, respectively, reserves of 0.074 and 0.101, respectively, and HBA of 0.027 and -0.036, respectively. These findings indicate that the production volume of coal mining companies is more determined by operational capacity, so that production increase strategies need to prioritize the development of operational capacity supported by the availability of resources and reserves.
Keywords: coal production volume; production costs; reference coal price; gmm; dynamic panel data